A Review of the Integrated Model of Care: An Opportunity to Respond to Extensive Palliative Care Needs in Pediatric Intensive Care Units in Under-Resourced Settings - Grunauer, Michelle; Mikesell, Caley (Frontiers in Pediatrics, 2018)
It is estimated that 6.3 million children who die annually need pediatric palliative care (PPC) and that only about 10% of them receive the attention they need because about 98% of them live in under-resourced settings where PPC is not accessible. The consultative model and the Integrated Model of Care (IMOC) are the most common strategies used to make PPC available to critically ill children. In the consultative model, the PICU team, the patient, or their family must request a PC consultation with the external PC team in order for a PICU patient to be evaluated for special care needs. While the consultation model has historically been more popular, issues related to specialist availability, referral timing, staff’s personal biases, misconceptions about PC, and other factors may impede excellent candidates from receiving the attention they need in a timely manner. Contrastingly, in the IMOC, family-centered care, PC tasks, and/or PC are a standard part of the treatment automatically available to all patients. In the IMOC, the PICU team is trained to complete critical and palliative care tasks as a part of normal daily operations. The present review investigates the claim that the IMOC is the best model to meet extensive PPC needs in PICUs, especially in low-resource settings; based on an extensive review of the literature, we have identified five reasons why this model may be superior. The IMOC appears to:1.) Improve the delivery of PPC and PCC, 2.) Allow clinicians to better respond to the care needs of patients and the epidemiological realities of their settings in ways that are consistent with evidence-based recommendations, 3.) Facilitate the universal delivery of care to all patients with special care needs, 4.) Maximize available resources, and 5.) Build local capacity; each of these areas should be further researched in order to develop a model of care that enables clinicians to provide pediatric patients with the highest attainable standard of healthcare. The IMOC lays out a pathway to provide the world’s sickest, most vulnerable children with access to PPC, a human right to which they are entitled by international legal conventions.